Contribution of Maharah Qira'ah Learning in Memorizing the Qur'an for Class IX Students of Mts. Pondok Pesantren Tahfidz Darul Qur'an Deli Serdang - Zakiah, Nur; Dermayani, Nur Zakiah Harahap; Fatma Yulia (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
When reading a verse, students frequently lose sight of its meaning or go to a similar verse. A contributing factor to this is a lack of proficiency in Arabic, particularly in reading. The purpose of this study is to determine how reading skills instruction at Tahfidz Islamic Boarding School Darul Qur'an Deli Serdang contributes to students' memorization of the Qur'an based on their actual experiences. This study employed a descriptive qualitative approach using observation, documentation, and interviewing as data collecting technique. The results showed that the contribution of learning reading skills in memorizing the Qur'an is in five aspects. First, improving reading accuracy. Second, improving understanding of meaning. Third, improving verse visualization. Fourth, increasing the speed of memorization. Fifth, improving the quality of student memorization. On that basis, learning reading skills has an important role in supporting the success of memorization. Based on these findings, it is recommended that reading skills learning be linked with the Qur'anic memory program to improve the effectiveness and comprehensiveness of the memorizing process.